Improving the efficiency of agricultural production econometric analysis based on price fluctuations - Kenjayev Toshbolta Aminovich, (THE INNOVATION ECONOMY, 2026)
This article presents an economic analysis of the importance of prices in managing the economy and regulating production in a market economy, as well as an econometric analysis of changes in the production of certain agricultural products in the Surkhandarya region based on price fluctuations.